CONDOM DISTRIBUTION STUDY: TENNESSEE DEPARTMENT OF HEALTH - Milholm, Jesseca (My University, 2019)
According to the Centers for Disease Control and Prevention (CDC), sexually transmitted diseases (STD) including chlamydia, gonorrhea and syphilis have been on the rise since 2013. Certain prevention programs have been implemented in order to lower these STD rates. One program in specific is condom distribution. This is a public health concern because STDs are increasing steadily in the state of Tennessee. I constructed a study to find the most effective way to distribute condoms to hopefully lower the new and reoccurring STD rates. Within three local county health departments I set up distribution sites and recorded condom uptake by counting each site weekly. Open containers with loose condoms available in restrooms and waiting areas with a “free condoms” sign showed to be the most successful form of distribution in these clinics. The traditional prepackaged brown paper bags of condoms displayed in easily accessible areas is another form of distribution compared to asking nurses for condoms. After 10 weeks of recording data within the health departments I gave the clinics recommendations on how to distribute condoms effectively and how many condoms should be ordered quarterly from the Tennessee Department of Health for their specific clinic.
Keywords: condoms; STD/HIV; public health